Impurezas Magnéticas em Ferromagnetos de Ising com Campo Transverso - Leite Filho, Raimundo Valmir (2015)
LEITE FILHO, Raimundo Valmir. Impurezas Magnéticas em Ferromagnetos de Ising com Campo Transverso. 2005. 109 f. Tese (Doutorado em Física) - Programa de Pós-Graduação em Física, Departamento de Física, Centro de Ciências, Universidade Federal do Ceará, Fortaleza, 2005. === Submitted by Edvander Pires (edvanderpires@gmail.com) on 2015-06-23T18:17:55Z No. of bitstreams: 1 2005_tese_rvleitefilho.pdf: 656815 bytes, checksum: af381150f33bff4b9142c5eeef4e117b (MD5) === Approved for entry into archive by Edvander Pires(edvanderpires@gmail.com) on 2015-06-23T21:06:49Z (GMT) No. of bitstreams: 1 2005_tese_rvleitefilho.pdf: 656815 bytes, checksum: af381150f33bff4b9142c5eeef4e117b (MD5) === Made available in DSpace on 2015-06-23T21:06:50Z (GMT). No. of bitstreams: 1 2005_tese_rvleitefilho.pdf: 656815 bytes, checksum: af381150f33bff4b9142c5eeef4e117b (MD5) Previous issue date: 2005 === A Green function formalism is used to calculate the spectrum of excitations associated with magnetic impurities implanted in a ferromagnetic thin film described by the transverse Ising model. Using the equations of motion method, explicit expressions for the Green function are determined for a ferromagnetic without impurities. The Green’s functions for a ferromagnetic film containing impurities are obtained through Dyson equation. We consider only the “defect” modes that appear below the bulk band of the pure material. In order to assess the influence of the position of the impurities in the film on the excitations spectra, we consider three different geometrical arrangement for the impurities: impurities line perpendicular to the surface film, four impurities in a plane paralel to the surface, and four impurities in a plane perpendicular to the surfaces of the film. We obtain results for the frequencies localized modes as a function of the exchange parameter between two impurities neighborings, of the exchange parameter between the impurities and their neighborings, and the effective field parameter at the impurities. === O formalismo de funções de Green é usado para calcular o espectro de excitações associados a impurezas magnéticas implantadas em um filme ferromagnético descrito pelo modelo de Ising com campo transverso. Através do método da equação de movimento expressões explícitas para as funções de Green são determinadas para um ferromagneto sem impurezas. A função de Green para um filme ferromagnético contendo impurezas é obtida através da equação de Dyson. O espectro de ondas de spin relativo ás impurezas é obtido para freqüências abaixo do limite inferior da banda de volume para um material puro. Com o objetivo de avaliar a influência da posição das impurezas no filme no espectro de excitações, consideramos três diferentes disposições geométricas para as impurezas: linha de impurezas perpendicular á superfície do filme, quatro impurezas em um plano paralelo `as superfícies e quatro impurezas em um plano perpendicular `as superfícies do filme. Obtemos resultados para a freqüência dos modos localizados como função do parâmetro de troca entre duas impurezas vizinhas, do parâmetro de troca entre as impurezas e seus vizinhos e do parâmetro de campo efetivo nas impurezas.